Microscopy and FTIR investigations of the thermal gelation of methylcellulose in glycols - Fahad, Muhammad; Gilbert, Marianne; Dickens, Phill (Pleiades Publishing, 2017)
Methylcellulose is a well-known polymer due to its reverse thermal gel formation property in aqueous solutions. Support materials play an important role in the additive manufacturing of three dimensional parts using processes that utilise inkjet technology. This paper presents novel compositions of methylcellulose (MC) in non-aqueous solvents and investigates the thermal gel formation of these compositions. Compositions containing MC in different glycols (ethylene, propylene and butylene glycol) were prepared. Suitability of these compositions as reusable support materials for jetting based three dimensional printing processes have been previously established. In this paper, the mechanism of gelation of MC in three different glycols is explained and compared using experimental techniques such as heating and cooling between 25–150°C, hot stage microscopy and Fourier Transform Infrared (FTIR) spectroscopy. Based on the results, a generalised gel formation diagram for MC in glycols is presented and compared with aqueous MC gel formation. The results showed that MC forms gels in glycols upon cooling and the temperatures of gel formation/melting are different for each glycol. Understanding of the gel formation of these compositions can help in fine tuning these compositions for their performance during three dimensional printing.